U-Pb dating of metamorphic monazite establishes a Pan-African age for tectonism in the Nallamalai Fold Belt, India - Sheppard, S.; Rasmussen, B.; Zi, J.; Soma Sekhar, V.; Srinivasa Sarma, D.; Ram Mohan, M.; Krapež, B.; Wilde, S.; McNaughton, Neal (Geological Society Publishing House, 2017)
© 2017 The Author(s). The Nallamalai Fold Belt comprises late Palaeoproterozoic to Mesoproterozoic sedimentary rocks deformed into a fold-and-thrust belt along the eastern side of Peninsular India. The age of thin-skinned thrusting, folding and low- to mediumgrade metamorphism in the belt is unclear, with estimates ranging from Palaeoproterozoic to early Palaeozoic. A possible Pan- African age for thrusting has previously been inferred from Rb-Sr dating of muscovite in shear zones from the adjacent Krishna Province (501 - 474 Ma) but these structures are separated from the Nallamalai Fold Belt by a major thrust. Here, we present in situ U-Pb dating of metamorphic monazite within a low-grade metasedimentary rock in the Nallamalai Fold Belt at the Mangampeta barite mine. Our date of 531 ± 7 Ma for the monazite is the first direct evidence that west- to NW-directed nappe stacking, folding and low-grade metamorphism in the fold belt are related to Pan-African incorporation of India into the Gondwana supercontinent.